Fostering Character Education in Pesantren: An Analysis of ‘Abd ar-Raḥmān Ḥabannakah’s Tadabbur Rules - Saleh, Muhammad; Rahmawati, Yeni; An-Nafi', Muhammad Bilal; Huda, Ade Naelul (Sekolah Tinggi Ilmu Ushuluddin Wadi Mubarak Bogor, 2025)
Character education is a crucial solution to the moral crisis among young people, with Islamic boarding schools (pesantren) serving as leading institutions for integrating religious values and local wisdom. This study analyzes the application of Abdurrahman Habanakah's Qur'anic tadabbur (contemplation) principles munasabah (intertextual coherence), asbabun nuzul (context of revelation), lughah (linguistics), balaghah (rhetoric), and ijtihad (independent reasoning) in character education within pesantren. This qualitative library research employs documentary analysis, focusing specifically on Surah Al-Isra: 23 and Al-Maidah: 8. The findings indicate that Habanakah's tadabbur approach effectively instills Qur'anic values such as birrul walidain (filial piety), justice, and piety through linguistic (lughah) and thematic (munasabah) analysis. The study concludes that integrating Qur'anic tadabbur into the pesantren curriculum strengthens religious textual understanding and fosters reflective and virtuous character among students. This research is limited to textual analysis of two selected verses; therefore, future studies could expand the scope to include more verses and empirical fieldwork to observe the direct application and impact of this method in pesantren settings. Abstrak Pendidikan karakter menjadi solusi penting dalam menghadapi krisis moral generasi muda, dengan pesantren sebagai institusi utama yang mengintegrasikan nilai-nilai agama dan kearifan lokal. Penelitian ini menganalisis penerapan kaidah tadabbur Al-Qur’an ‘Abd ar-Raḥmān Ḥasan Ḥabannakah al-Maidānī (w. 2004) meliputi munāsabah, asbāb an-nuzūl, luġah, balāġah, dan ijtihād dalam pendidikan karakter di lingkungan pesantren. Penelitian kualitatif kepustakaan ini menggunakan analisis dokumen dengan fokus pada QS. Al-Isrā’/17: 23 dan Al-Mā’idah/5: 8. Hasil penelitian menunjukkan bahwa pendekatan tadabbur Habanakah efektif menanamkan nilai-nilai Qur’ani seperti birr al-wālidain, keadilan, dan ketakwaan melalui analisis kebahasaan (luġah) dan tematik (munāsabah). Disimpulkan bahwa integrasi tadabbur Al-Qur’an ke dalam kurikulum pesantren tidak hanya memperdalam pemahaman teks keagamaan tetapi juga membentuk karakter santri yang reflektif dan berakhlak mulia. Penelitian ini terbatas pada analisis tekstual dua ayat pilihan; sehingga kajian lanjutan dapat memperluas cakupan ayat yang dikaji dan melakukan penelitian lapangan untuk mengamati penerapan serta dampak metode ini secara langsung di pesantren.